What Is the Best Treatment of the Femoral Shaft Nonunion after Intramedullary Nailing? A Systematic Review - Luca Bianco Prevot; Alessandra Nannini; Laura Mangiavini; Andrea Bobba; Sara Buzzi; Federico Sinigaglia; Giuseppe Peretti (Life, 2023)
Nonunion (NU) is one of the most feared complications of femoral shaft fracture treatment. Femoral shaft fracture treatment is often linked with poor bone stock and reduced bone metabolism. In this paper, the goal is to carefully analyze the best treatment options for patients who developed nonunion after the intramedullary nailing of a femoral shaft fracture. A systematic review of the literature available in the PubMed, EMBASE and Cochran library databases was carried out, and 16 studies were included. Exclusion criteria included case reports and case series that do not have data about clinical outcomes or functional outcomes and included fewer than 10 patients. The reviewed data provide evidence for very good results about the treatment of this pathology with exchanging intramedullary nails or the implantation of a plate and screws (general healing rate of 96.3%). Moreover, the data support the utilization of autologous bone graft in order to stimulate the healing process. In conclusion, the choice between these two types of treatment must be guided by the type of pseudarthrosis that the patient presents. Additionally, bone grafting or growth factors promote bone regenerative processes, especially in patients with oligo-atrophic pseudoarthrosis.